Antibacterial activity of propolis collected in different regions of Brazil - Gonsales, G. Z. [UNESP]; Orsi, R. O. [UNESP]; Fernandes Júnior, A. [UNESP]; Rodrigues, P. [UNESP]; Funari, S. R. C. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2006)
The aim of this study was to investigate the antibacterial activity of propolis samples from Goiás, Paraná and São Paulo States, Brazil, and their flavonoids content. Ethanolic extracts of propolis (EEP) were prepared (30g of propolis in 70% ethanol), and the microorganisms Staphylococcus aureus and Escherichia coli were tested. The methodology employed was agar diffusion using filter paper discs. Ampicillin and tetracycline were used as controls. Antibacterial activity was determined by the reading of inhibition zone diameters (mm) after 24 hours incubation at 37°C. Results demonstrated that EEP inhibited the growth of Staphylococcus aureus but not that of Escherichia coli. Tetracycline and ampicillin showed an efficient action against both bacteria. Flavonoids content was variable, depending on the propolis sample. According to the results, it may be concluded that EEP showed effective action against Gram-positive bacteria, independently on their geographic origin, and a positive correlation between antibacterial activity and flavonoids content.
Keywords: propolis; antibacterial activity; flavonoids